Raising race questions : whiteness and inquiry in education - Michael, Ali. (New York : Teachers College Press, 2015)
Provides a process for developing questions about race that eead to growth and change, as well as a vision for where engagement with race questions might lead.
Introduction : white teaching, whole classrooms. Guiding principles of this book ; In the field ; Road map for the book ; Teachers -- Raising race questions and managing the inquiry impasse. Questions about teaching, pedagogy, and logistics ; Questions about students as racial beings ; Questions about oneself as a teacher ; The inquiry impasse ; Strategies for raising race questions -- Racial identity is not just another tool, it's the toolbox. What's positive about being white? : teacher racial identity matters ; Navigating racial adolescence ; Strengthening the toolbox : building a positive white racial identity -- A multicultural curriculum is not sufficient for building an antiracist classroom. The students have windows and mirrors, but they still don't fit in . . . . : building an antiracist kindergarten ; The curriculum is multicultural, but the AP class is not building an antiracist classroom -- Talking about race in the classroom. Challenging the idea that talking about race is racist ; Racial socialization -- From theory to practice to theory : facilitating inquiry. Keeping the focus on race ; Storytelling ; Tracking, both internal and external ; Support and confront ; Strengthen your own toolbox ; Learning from conflict ; Group dynamics ; Nuts and bolts -- Appendix A : responses from teachers -- Appendix B : resources for use in race inquiry -- Appendix C : research models.
Includes bibliographical references and index.
Keywords: White people -- Race identity -- Study and teaching -- United States; Multicultural education -- United States; Race awareness -- Study and teaching -- United States; Racism in education -- United States; United States -- Race relations; Black people -- Race identity -- Study and teaching -- United States; Multicultural education; Race awareness -- Study and teaching; Race relations; Racism in education; Whites -- Race identity -- Study and teaching; United States